FACTORS RELATED TO SEXUAL HARASSMENT ON PUBLIC TRANSPORTATION IN JABODETABEK IN 2022 - Mutia Ayu Putri Setiawan; Istianah Surury (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Komnas Perempuan defines sexual harassment as sexual acts through physical or non-physical touch with the sexual organs or sexuality of the victims they are subjected to, including acts of whistling, flirting, sexually suggestive speech, displaying pornography and sexual desires, touching or touching the body, gestures or gestures of a sexual nature that result in discomfort, offense, feeling degraded, and possibly to the point of causing health and safety issues. One of them was (55.7%) of respondents who had experienced sexual harassment on public transport. The most respondents who were exposed to the most sexual harassment were women (75.2%). The most frequent harassment was in the KRL (19.5%). The most frequent abuse was verbal abuse (47.7%). The most common type of verbal abuse is someone who calls beautiful/handsome sweet etc. (42.3%). The most perpetrators were other passengers (36.9%). The purpose of this study is that this research was conducted to determine the experience of sexual harassment in general transportation users in Jabodetabek in 2022. The method used This research is a type of quantitative research with a descriptive observational approach with a cross-sectional study design. Data collection was carried out primer using a questionnaire with a sample of 149 respondents taken by purposive sampling technique. The advice of every public transport officer is to provide strict protection so that there is no more sexual harassment.